Managing Ethical Challenges to Mental Health Research in Post‐Conflict Settings. Issue 1 (8th January 2015) - Chiumento, Anna; Khan, Muhammad Naseem; Rahman, Atif; Frith, Lucy
Abstract: Recently the World Health Organization (WHO) has highlighted the need to strengthen mental health systems following emergencies, including natural and manmade disasters. Mental health services need to be informed by culturally attuned evidence that is developed through research. Therefore, there is an urgent need to establish rigorous ethical research practice to underpin the evidence‐base for mental health services delivered during and following emergencies.